A banana fruit transcriptional repressor MaERF10 interacts with MaJAZ3 to strengthen the repression of JA biosynthetic genes involved in MeJA-mediated cold tolerance - Qi, Xin-na; Xiao, Yun-yi; Fan, Zhong-qi; Chen, Jian-ye; Lu, Wang-jin; Kuang, Jian-fei (Postharvest biology and technology, 2016)
•Expression of MaERF10 is inhibited by MeJA treatment.•MaERF10 suppresses the expression of JA biosynthetic genes by directly binding to their promoters.•MaERF10 physically interacts with MaJAZ3.•MaERF10 coordinates with MaJAZ3 to strengthen the repression of JA biosynthetic genes. Bananas are easily subject to chilling injury (CI) when stored at temperatures below 13°C and methl jasmonate (MeJA) application is known to alleviate CI symptoms of the fruit. However, the underlying regulatory mechanisms of these processes remain largely unknown. In this study, we identified a transcriptional regulator, MaERF10, which was repressed by MeJA treatment in banana fruit under low temperature storage. Electrophoretic mobility shift assays (EMSA) and transient expression analyses indicated that MaERF10 was able to bind to and suppress the promoters of several JA biosynthetic genes, such as MaLOX7/8, MaAOC3, and MaOPR4, whose transcripts were MeJA-inducible. More importantly, yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays confirmed that MaERF10 physically interacted with MaJAZ3, a repressor of JA signaling, and the interaction led to deeper repression of JA biosynthetic genes by MaERF10. Taken together, these findings suggest that MaERF10 may act as a transcriptional repressor to modulate MeJA-induced cold tolerance of bananas possibly through recruiting MaJAZ3 to strengthen the repression of JA biosynthetic genes, which provides new insights into a transcriptional regulatory network of MeJA-induced cold tolerance of banana fruit.